LSKE: Lightweight Secure Key Exchange Scheme in Fog Federation. (25th October 2021) - Salami, Yashar; Khajehvand, Vahid
Abstract : The fog computing architecture allows data exchange with the vehicle network, sensor networks, etc. However, before exchanging data, the nodes need to know each other and key exchange. Yashar et al. recently proposed a secure key exchange scheme for the fog federation. However, their proposed scheme has a high computational overhead and is not suitable for fog federation. Therefore, we have proposed a lightweight, secure key exchange scheme for the fog federation to reduce computational overhead. To prove the lightweight, we have compared the proposed scheme with the Yashar design in terms of computing, and communication cost AVISPA Tool was used for the formal analysis of the proposed scheme. Then, we simulated the proposed scheme with the NS3 tool and compared it with Throughput, packet loss, Packet Delivery, and end-to-end delay with Yashar et al. scheme. The results show that the proposed design reduced 3.2457 ms of computational overhead and 1, 024 transmitted data bits.